(untitled) (Journal of Asian Development Studies, 2024)
This study aims to find out the relationship between secondary school teachers’ technical skills and their instructional competencies. It also seeks to understand the obstacles that keep teachers from utilizing technology and how they view their instructional competencies and information technology skills. The research also investigated the relationship between teachers’ information technology skills and job proficiency. The study addresses the diverse landscapes among teachers and promotes broader technology adoption in assessment and evaluation. The concerns that have been identified include those linked to technology, students, and families, which emphasizes the necessity of making infrastructural upgrades and providing thorough training. The study highlights the significance of motivation and attendance in online learning, consistent with previous research. Teachers emphasize in-service training and skill development, expressing a common sense of inadequacy in technological integration. The study used a questionnaire to gather information from secondary school teachers as part of a quantitative research approach. The study’s conclusion sheds light on how information technology might help teachers do better at work and develop their instructional competencies. The findings might also be useful in devising ways to get around obstacles that hinder teachers from using technology in the classroom.